Privacy-Preserving IoT Data Management with Blockchain and AI - A Scholarly Examination of Decentralized Data Ownership and Access Control Mechanisms (Internet of Things and Edge Computing Journal, 2021)
This paper explores the intersection of privacy-preserving techniques, blockchain technology, and artificial intelligence (AI) in managing Internet of Things (IoT) data. The proliferation of IoT devices has led to an exponential increase in the generation of sensitive data, raising concerns about privacy and security. Traditional centralized data management systems are often vulnerable to attacks and breaches. To address these challenges, this paper investigates the use of blockchain and AI to create decentralized data management systems that prioritize privacy and security. The study evaluates various decentralized data ownership and access control mechanisms, highlighting their effectiveness in enhancing privacy and security in IoT environments. Through a comprehensive analysis, this paper aims to provide insights into the benefits and challenges of implementing such systems and their potential impact on future IoT deployments.